Business Driven Technology - Phillips Amy (McGraw -Hill, 2005)
BDT takes a business-first approach, improving students' perception of the value of IS within the business discipline. This perspective allows instructors to more easily demonstrate how technology and systems support business performance and growth. The adaptive chapter/plug-in organization enables the instructor to adjust content according to their business or technical preferences.